STRENGTHENING COMMUNITY-BASED PRIMARY HEALTH CARE MANAGEMENT THROUGH FIELD LEARNING AND COMMUNITY ENGAGEMENT AT PRIMARY HEALTH CENTER: STRENGTHENING COMMUNITY-BASED PRIMARY HEALTH CARE MANAGEMENT - Cici Apriza Yanti; Desri Nova; Tika Ramadanti; Abdi Iswahyudi Yasril (Community Service Journal of Indonesia, 2026)
Community-based primary health care remains a strategic approach to improving population health outcomes, particularly in strengthening health service management at the primary level. This community service activity was conducted at Padang Tarok Primary Health Center and its surrounding community through a field-based learning and community engagement program involving public health students. The activity aimed to analyze health service management, identify priority health problems, and implement community-oriented interventions in collaboration with health workers and local stakeholders. The program was carried out through several stages, including situation analysis, problem identification, priority setting, intervention planning, implementation, and evaluation. Community members and health personnel actively participated in health education, environmental health activities, and service management discussions. The results showed improved community awareness of health issues, strengthened collaboration between academic institutions and primary health care services, and enhanced students’ practical competencies in public health management. This activity demonstrates that structured community service programs integrated with primary health care settings can effectively support health system strengthening and community empowerment.